2023
DOI: 10.1101/2023.01.11.521715
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systemic orchestration of cell size throughout the body: Influence of sex and rapamycin exposure inDrosophila melanogaster

Abstract: Along with differences in life histories, metazoans have evolved vast differences in cellularity, involving changes in the molecular pathways controlling the cell cycle. The extent to which the signalling network systemically determines cellular composition throughout the body and whether tissue cellularity is organized locally to match tissue-specific functions are unclear. We cultured genetic lines of Drosophila melanogaster on food with and without rapamycin to manipulate the activity of TOR/insulin pathway… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The datasets, R code and materials supporting this article have been uploaded as part of the electronic supplementary material [76]. The early version of the manuscript was deposited at bioR X iv -the preprint server for Biology: https://doi.org/10.1101/ 2023.01.11.521715 [77].…”
Section: Discussionmentioning
confidence: 99%
“…The datasets, R code and materials supporting this article have been uploaded as part of the electronic supplementary material [76]. The early version of the manuscript was deposited at bioR X iv -the preprint server for Biology: https://doi.org/10.1101/ 2023.01.11.521715 [77].…”
Section: Discussionmentioning
confidence: 99%
“…For example, at high temperatures, small-celled fish species were found to tolerate hypoxia better than large-celled species [27]. In other studies, small-celled forms of adult D. melanogaster were induced developmentally by larval feeding with rapamycin, a drug that downregulates the activity of the TOR kinase in TOR complex 1, reducing downstream signalling coming from this part of the TOR/insulin pathways [63,64]. The small-celled flies in these studies showed better flight performance under hypoxia than large-celled flies, and this effect was temperature-dependent [26], but they suffered increased mortality during early adulthood [63].…”
Section: Discussionmentioning
confidence: 99%